Agerelated parameters of P300 auditory evoked potentials in elderly persons in the context of cognitive health: A study in the European North of Russia - L. V. Poskotinova; E. V. Krivonogova; O. V. Krivonogova; A. V. Kudryavtsev (Acta Biomedica Scientifica, 2024)
Background. Setting of norms for the parameters of P300 cognitive auditory evoked potentials (EP) in elderly people with intact cognitive functions considering their residence in certain climatic and geographical regions is an urgent problem.The aim of the study. To determine age-related parameters of P300 cognitive auditory evoked potentials in elderly people aged 60–69 and 70–74 years, living in the European North of Russia (using the example of Arkhangelsk).Methods. The parameters of P300 auditory EP were determined in randomly selected urban residents in the age groups of 60–69 years (n = 284) and 70–74 years (n = 115) with normal scores on the Montreal Cognitive Assessment Scale (MoCA), without depression (according to Beck Depression Inventory), with preserved ability to work and/or social functions. We calculated the 5th–95th percentile values (P5– P95) of the P300 EP parameters and assessed the relationships of these parameters with socio-demographic characteristics, lifestyle and the results on the MoCA scale and Beck Depression Inventory.Results. Statistically significant differences in latency indicators of P300 EP were determined between groups of 60–69 and 70–74 years (P25–P90) in all studied brain regions (frontal, central). In the group of 60–69 years, the range of P25–P75 values of P300 EP latencies was 342.5–401 ms, in the group of 70–74 years – 358.5–443 ms. Age differences in P300 EP amplitudes were minimal with an interquartile range of 4–13 μV in the total sample. Participants who smoked had higher latency scores and lower amplitude scores; former smokers had higher latency scores compared to never-smokers.Conclusion. Latency above 400 ms at the age of 60–65 years and above 443 ms at 70–74 years can be considered as a criterion for reduced cognitive reserve and an increased risk of developing cognitive disorders in elderly people living in the European North of Russia.